The Influence of Using Interactive Learning Media Wordwall on the Learning Motivation in Fourth Grade Elementary School Students - Sinta Sinta; Ahmad Rustam; Ahmad Ahmad (Journal of Education and Learning Sciences, 2025)
Learning motivation is an important factor in supporting students' active participation and achievement in elementary education. However, the use of interactive digital learning media to strengthen students' motivation remains limited in some elementary school classrooms. This study aimed to examine the effect of Wordwall as an interactive learning medium on the learning motivation of fourth-grade students at SD Negeri 6 Kendari. The novelty of this study lies in the application of Wordwall as a game-based and interactive digital learning medium specifically to improve learning motivation among fourth-grade elementary school students in the local context of SD Negeri 6 Kendari, as well as in the comparison of its effectiveness with conventional learning methods. This study employed a quantitative approach with a quasi-experimental design using a nonequivalent control group. The participants consisted of 70 fourth-grade students, with 35 students assigned to the experimental group and 35 students to the control group. Data were collected using a learning motivation questionnaire and analyzed using descriptive statistics, N-Gain analysis, paired-samples t-test, and independent-samples t-test. The results showed that the mean learning motivation score in the experimental group increased from 31.31 in the pretest to 42.46 in the posttest, with a mean N-Gain score of 0.68, categorized as moderate. In comparison, the control group obtained a mean N-Gain score of only 0.18, categorized as low. The paired-samples t-test yielded a significance value of 0.000 (p < 0.05), indicating a significant increase in the experimental group's learning motivation. Furthermore, the independent-samples t-test produced a significance value of 0.000 (p < 0.05), confirming a significant difference between the experimental and control groups. These findings indicate that Wordwall is more effective than conventional learning methods in increasing elementary school students' learning motivation. Therefore, Wordwall has the potential to serve as an innovative, interactive, and game-based digital learning medium for strengthening students' motivation and active engagement in elementary education.